No indication of arthropod-vectored viruses in mosquitoes (Diptera: Culicidae) collected on Greenland and Svalbard. - Müllerová, Jana (Jihočeská univerzita, 2018)
Arboviruses are a large polyphyletic group of viruses being transmitted from arthropod vectors to vertebrate hosts. They are important human and animal pathogens. Among the most famous representatives of arboviruses include the Tick-borne encephalitis virus (TBEV), Dengue virus (DV), Zika virus (ZIKV) or Rift Valley fever virus (RVFV) etc. They are studied in tropical and temperate zones abundantly. However, in polar regions there are no traces of such viruses, despite climate change and the migration of vectors to higher latitudes. Therefore, the knowledge of potential worldwide occurrences of arboviruses is important due to their potential to be pathogenic for humans. Arboviruses were detected in many countries such as Alaska, Norway, Canada and in North America, but never in Svalbard nor in Greenland. This research study was focused on the monitoring of arboviruses in north Atlantic areas. Thousands of samples from the mosquito species Aedes nigripes were examined, both from Greenland and from Svalbard (collected during the years 2012-2016). I tested these samples for the presence of different arboviral genera; Orthobunyavirus, Orbivirus, Flavivirus, Alphavirus, Phlebovirus. No presence of arboviruses in examined mosquitoes were detected. These results may reflect an absence of arboviruses, or their prevalence is under the detection limit of our screening in areas studied.
No indication of arthropod-vectored viruses in mosquitoes (Diptera: Culicidae) collected on Greenland and Svalbard.